The Geopolitics of South Asia : From Early Empires to the Nuclear Age - Chapman, Graham P. (Aldershot, England Ashgate Publishing Limited, 2003)
His volume tells the story of the Indian sub-continent. It shows how geological movements mounded the land and explores its history, from the early settlers, the Mogul Empire and the Raj, through the impact of railways, the development of irrigation systems and the spread of democracy.
Includes Maps, bibliography, Illustrations, References and Index.
Keywords: Geopolitics -- South Asia -- Asia